2-Oxoglutarate regulates binding of hydroxylated hypoxia-inducible factor to prolyl hydroxylase domain 2. Issue 25 (9th March 2018) - Abboud, Martine I.; McAllister, Tom E.; Leung, Ivanhoe K. H.; Chowdhury, Rasheduzzaman; Jorgensen, Christian; Domene, Carmen; Mecinović, Jasmin; Lippl, Kerstin; Hancock, Rebecca L.; Hopkinson, Richard J.; Kawamura, Akane; Claridge, Timothy D. W.; et al.
Abstract : The binding of prolyl-hydroxylated HIF-α to PHD2 is hindered by prior 2OG binding; likely, leading to the inhibition of HIF-α degradation under limiting 2OG conditions. Abstract : Prolyl hydroxylation of hypoxia inducible factor (HIF)-α, as catalysed by the Fe(ii )/2-oxoglutarate (2OG)-dependent prolyl hydroxylase domain (PHD) enzymes, has a hypoxia sensing role in animals. We report that binding of prolyl-hydroxylated HIF-α to PHD2 is ∼50 fold hindered by prior 2OG binding; thus, when 2OG is limiting, HIF-α degradation might be inhibited by PHD binding.